Virtual Learning Challenges for Special-needs Students: Study in Early Elementary School Age during the Covid-19 Pandemic - Ribut Prastiwi Sriwijayanti; Afib Rulyansah (STAI Hubbulwathan Duri, 2022)
Students with special needs at seven private primary schools in Probolinggo Regency, Indonesia, are the focus of this research, which aims to identify the challenges they confront throughout the distance learning process. A case study approach was used in this research. The participants in this research were seven parent-teacher pairs. Demographic data were collected in this research and an interview was conducted using a standard format. This research used content analysis as an analytical approach. Standardized interviews have shown that academic, social-emotional, and linguistic development are the most common issues that parents and teachers encounter in their work with children. On the other hand, educational difficulties were often associated with classroom involvement. According to the findings of this study, children with special needed have difficulty developing academically, socially, and linguistically. It revealed that inclusive students struggle with technology use, participation in online classes, and attention management.